Migration transitions - de Haas, H (International Migration Institute, 2010)
This paper aims to advance a conceptual framework on the developmental drivers of international migration processes and to provide an empirical test drawing on the global migrant origin database. Conventional ideas that development in origin countries will reduce international migration are ultimately based on “push-pull”, neoclassical and other equilibrium models which assume an inversely proportional relationship between absolute levels and relative differences of wealth and migration. By contrast, another group of theories postulate that development leads to generally increased levels of migration and that societies go through migration transitions characterised by an inverted U-shaped pattern of emigration. The paper discusses as yet unobserved conceptual parallels and differences between separately evolved ‘transition’ theories. It subsequently amends and synthesises prior theories, based on a criticism of their evolutionary character and sedentary bias, their inclination towards demographic determinism, their limited conceptualisation of structure and agency as well as the causal mechanisms underlying the correlations they describe. Sen’s capabilities-based development concept is applied to migration to create analytical room to analyse most forms of migration within a single perspective. Structure and agency are incorporated by conceptualising migration as a function of (1) capabilities, (2) aspirations and, on a macro-level, (3) opportunity rather than income differentials. Because of the contested nature of migration transition theory, the paper provides an empirical test. Drawing on the World Bank/University of Sussex global migrant origin database, it estimates the effect of theoretically relevant development indicators on immigrant, emigrant, net immigrant and total migrant stocks. The results largely confirm transition theory. Higher levels of economic and human development are associated to higher overall levels of migration and have the predicted U-curve effect on emigration. The results also suggest that demographic factors do not have a direct effect on migration. Although several empirical puzzles remain, particularly on the effects of political freedoms, the results suggest that take-off development in the least developed countries is likely to lead to take-off emigration. The analysis exemplifies the need to conceptualise migration as an integral part of broader development processes rather than as problem to be “solved”.